Level of heavy metals in marine stingrays (chondrichthyes: dasyatidae) landed from Johor Waters, Malaysia - Chong, Weini; Adiana, G.; Baharom, I. N.; Yunus, Kamaruzzaman; Takarina, N. D.; Ong, Meng Chuan (Elsevier Ltd, 2024)
Heavy metal pollution in aquatic ecosystems can lead to harmful accumulation in organisms like stingrays, posing potential health risks to humans. To assess this risk, 45 stingrays were sampled from Johor Waters (Pontian, Muar, and Batu Pahat) and analyzed for heavy metal content using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The average concentrations of Cu, Zn, As, Cd, Pb, and Hg in the fillets were 0.982 ±0.637, 31.3±5.93, 93.57±24.5, 0.039±0.047, 0.158±0.036, and 0.592±0.424 μg/g dw, respectively. Arsenic (As) was found at the highest concentration. The study indicates that fish size does not directly influence heavy metal accumulation and that metal levels vary by location. Calculated consumption limits for different metals are crucial for human safety. This data is valuable for evaluating contamination risks and guiding future research to protect marine ecosystems in Johor Waters.